Pengaruh AI Mindset Positif terhadap Kesiapan Kerja Akuntan 5.0 Mahasiswa Pendidikan Akuntansi melalui Experiential Learning dan Soft Skill sebagai Mediator - siti_kusuma; Amirul Arif (FKIP, Universitas Banten Jaya, 2026)
This study aims to look at how the AI mindset positive of students in the Accounting Education Program at Surabaya State University affects their readiness for Accountant 5.0 jobs.It also considers how Experience-Based Learning and Soft Skills play a role in this relationship. This study used a quantitative method involving surveys, where questionnaires were given to students who were enrolled during the 2022 and 2023 school years. A total of 172 participants were chosen through purposive sampling. The data were analyzed with SEM-PLS, which is a version of SmartPLS, to perform structural equation modeling. Based on the results, having a positive attitude towards AI does not directly affect someone's readiness for work as an accountant. However, when it comes to learning through experience and developing soft skills, having a positive attitude towards AI is a valuable extra benefit. Accountant 5.0 Job Readiness is closely linked to Experience-Based Learning and Soft Skills, and this connection is both helpful and supported by statistical evidence. The mediation test results showed that Experience-Based Learning and Soft Skills completely influenced how a positive mindset toward AI affected Accountant 5.0 Work Readiness. According to the study's findings, students' views on AI, their hands-on learning experiences, and their non-technical abilities are the key factors that influence how prepared they are for work. Higher education institutions can use this research to help their students get better ready for jobs in the Society 5.0 era by including lessons on artificial intelligence, hands-on experience, and soft skills in their courses